Ways of Organizing Innovative Processes in Our Republic - Shavkatovna, Komilova Mukammal; Khikmatovna, Turayeva Malika; Azamovna, Djuraeva Makhzuna (Miasto Przyszłości, 2024)
The article presents the views of foreign and domestic scientists on the concepts of innovation and its essence. A detailed theoretical analysis of the forms of organization of innovative processes and the main stages of innovative processes is given. As a result of the analysis, the term "innovation" was defined by the author. The strategic directions of the effective organization of innovative processes in the Republic of Uzbekistan are presented.